Early intestinal microbiota changes in aged and adult mice with sepsis - Yuan, Yangyang; Liu, Shaohua; Ding, Xianfei; Li, Ying; Zhang, Xiaojuan; Song, Heng; Qi, Xueyan; Zhang, Zihao; Guo, Kaiyuan; Sun, Tongwen (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract The mortality rate associated with sepsis in elderly individuals is higher than that in younger individuals. The intestinal microbiota has been demonstrated to play an important role in the occurrence and development of sepsis. The purpose of this study was to investigate the differences in the intestinal microbiota between aged and adult mice with sepsis. We purchased thirty male C57BL mice (6-8 weeks) from Beijing Vital River Laboratory Animal Technology (Beijing, China). They were randomly divided into two groups: 15 in the adult group (AD group) and 15 raised to 20-21 months in the age group (Age group). All the mice underwent caecal ligation and puncture to induce sepsis. Rat faeces were analysed using 16S rDNA sequencing. Compared with adult sepsis mice, the levels of inflammatory factors in the aged mice increased, the diversity of the intestinal microbiota decreased significantly, and the structure of the dominant intestinal microbiota changed. In the Age group, the microbiota associated with inflammatory factors increased, and the microbiota associated with the production of SCFAs (Ruminiclostridium, Prevotellaceae_UCG-001, Rikenella, Parabacteroides, Oscillibacter, Odoribacter, Muribaculum, Lachnoclostridium, Intestinimonas, Faecalibaculum, Anaerotruncus and Alloprevotella) decreased significantly. The metabolic pathways related to the microbiota also changed significantly. Our study also found that the Aged group exhibited more anaerobic, facultative anaerobic and more gram-positive bacteria. Our results showed that there were significant differences in the abundance and structure of microbiota between aged and adult sepsis mice. Keywords: sepsis, intestinal microbiota, aged mice